Cattle breed improvement for sustainable draft power use in Ethiopian agriculture - Tegegne, Azage (Ethiopian Agricultural Research Organization, 1998)
Ethiopia has the largest livestock population in Africa with approximately 30 million cattle, of which 9 to 10 million oxen are used for draft purposes. About 85 percent of the estimated 55 million human population lives in rural areas, with agriculture as the primary occupation. About 90 percent of these rural communities use draft animals for various purposes. Among farmers who use draft animal power, about 29 percent have a pair, 8 percent three or more, 34 percent have one and 29 percent have no oxen. Access to draft power at specific time of the year can therefore be a key factor influencing the crop agriculture. The Ethiopian highlands represent 40 percent of the total land mass of 1,098,000 km2 and is inhabited by about 90 percent of the human population. The main purpose of keeping cattle in the highlands is for draft power, and it is estimated to account for about 60 percent of the cattle product by value. In crop production, draft oxen are estimated to contribute to more than 26 percent of the total labour requirements. About 66 percent of the country's 14 million crop land is cultivated with the use of animal power. The average land size in the highlands is about 2.5 hectares and land preparation and subsequent cultivation is done primarily with a pair of oxen drawing the maresha. It is estimated that herds of 8 to 10 cattle have to be kept by individual farmers at any one time to ensure availability of a pair of working oxen during land cultivation. The major feed resources that support livestock in the highlands include about 23 million hectares of grazing land and crop residues. Zebu oxen are the main animals used for tillage and threshing. In some areas where oxen are in short supply, horses, mules and donkeys are either hitched with the same species or in mixed pairs. Sometimes oxen are paired with equine or barren cows for ploughing. Oxen work for about 2 months per year, although the work potential of draft cattle can be 8 to 10 months as is estimated in India. The non-use of oxen for transport and other task during the long non-cultivation period is one of the reasons for the low utilization of oxen in Ethiopia. In the last three decades to 1991, food production per head fell steadily, mainly as a result of civil war, soil exhaustion, erosion and over-population in the marginal highland agrarian areas. This created dependence on food imports ranging from 100,000 tons in 1980 to 1 million tons in 1995/96 as a result of favourable weather and intervention. However, the growing scale of the structural food deficit indicates that the country needs to produce an extra 320,000 tons of food per year simply to keep pace with population growth. Almost all the food production is dependent on mainly draft oxen which plough a total land area of about 7 million ha, generating a total power output of 250,566,840 kwh per year. The draft power generated for ploughing per year would be equivalent to about 27 percent of the total amount of electricity sold in the country. Availability of oxen and their work efficiency could have substantial impact of food production. In this paper, the use and requirements are examined and possible areas that need improvement are suggested and discussed.